European and Chinese territoriality and territorial identity: temporal and spatial comparision of the post-war situation in Europe - Joel Peetersoo (European Regional Science Association (ERSA), 2001)
The number of territorially based identities, that every human being has, is countless. Tied with different scales and natures of territorial units, the clearest of them appear to be political, economical and cultural identities of macro-, meso- and microscale. What are possibly the most important territorial identities of the global province known as Europe? Could these determine the developing trend for all world or are they affected by globalization themselves? And what does look like the development of the identities of China, the claimed to be antagonist of the western civilization, in this light – similar, cross-different or something in between?
Keywords: 330